Evaluating modified atmosphere with variable CO₂-O₂ concentrations for Tribolium castaneum management and quality preservation in Rice storage - Xue Dong; Ming Yang; Peian Tang (Food Chemistry: X)
This study explored the efficacy of CO₂-MA with variable CO₂-O₂ concentrations (TA: 2 % O₂ + 35 % CO₂, TB: 14 % O₂ + 35 % CO₂, TC: 21 % O₂ + 35 % CO₂, TD: 21 % O₂ + 60 % CO₂) in controlling Tribolium castaneum and preserving rice quality. TD exhibited the highest efficacy, achieving rapid and complete pest mortality within 48 h, particularly in the resilient pupal stage, and nearly 100 % mortality under grain-embedded conditions within 10 days. Quality assessments revealed that TD effectively mitigated lipid oxidation by reducing aldehydes and alcohols, major contributors to rice aging and off-flavors while maintaining acceptable enzymatic activities and VOC profiles. Principal component analysis confirmed that TD minimized oxidative stress and preserved desirable sensory attributes more effectively than hypoxic treatments. These findings presented an advancement in sustainable grain storage, with tailored CO₂-O₂ ratios to achieve desirable outcomes as a sustainable strategy for long-term rice storage.